Effect of a single acupuncture treatment on surgical wound healing in dogs: a randomized, single blinded, controlled pilot study - Saarto, Erja E. [UNESP]; Hielm-Bjorkman, Anna K.; Hette, Khadije [UNESP]; Kuusela, Erja K.; Brandão, Claudia Valeria Seullner [UNESP]; Luna, Stélio Pacca Loureiro [UNESP] (Biomed Central Ltd., 2010)
Background: The aim of the study was to investigate the effect of acupuncture on wound healing after soft tissue or orthopaedic surgery in dogs.Methods: 29 dogs were submitted to soft tissue and/or orthopaedic surgeries. Five dogs had two surgical wounds each, so there were totally 34 wounds in the study. All owners received instructions for post operative care as well as antibiotic and pain treatment. The dogs were randomly assigned to treatment or control groups. Treated dogs received one dry needle acupuncture treatment right after surgery and the control group received no such treatment. A veterinary surgeon that was blinded to the treatment, evaluated the wounds at three and seven days after surgery in regard to oedema (scale 0-3), scabs (yes/no), exudate (yes/no), hematoma (yes/no), dermatitis (yes/no), and aspect of the wound (dry/humid).Results: There was no significant difference between the treatment and control groups in the variables evaluated three and seven days after surgery. However, oedema reduced significantly in the group treated with acupuncture at seven days compared to three days after surgery, possibly due the fact that there was more oedema in the treatment group at day three (although this difference was nor significant between groups).Conclusions: The use of a single acupuncture treatment right after surgery in dogs did not appear to have any beneficial effects in surgical wound healing.